Daytime sleepiness: a risk factor for poor social engagement among the elderly. Issue 4 (28th October 2013) - Lee, Yao‐Tung; Tsai, Chia‐Fen; Ouyang, Wen‐Chen; Yang, Albert C.; Yang, Cheng‐Hung; Hwang, Jen‐Ping
Abstract Background The aim of this study was to investigate the relationship between social engagement and daytime sleepiness among aged residents of a veterans' housing facility in Taiwan. Methods A total of 597 men were enrolled in this cross‐sectional study. Each subject was assessed with the Resident Assessment Instrument‐Minimum Data Set, Geriatric Depression Scale, Pittsburgh Sleep Quality Index, and Mini‐Mental State Examination. Social engagement was measured with the Index of Social Engagement (ISE), and daytime sleepiness was defined according to the relevant Pittsburgh Sleep Quality Index subcomponent. Subjects were divided into two groups according to their ISE levels. A multivariate logistic regression model was used to examine the association between ISE and other variables. Results The sample's mean age was 80.8 ± 5.0 years (range: 65–99 years). Mean ISE score was 1.5 ± 1.3 (range 0–5), with 52% of participants reporting poor social engagement (ISE = 0–1). Mean Pittsburgh Sleep Quality Index global score was 5.6 ± 3.6 (range: 0–18), and 31% of participants reported daytime sleepiness. The analysis was adjusted for level of depression, cognitive impairment, dependence in activities of daily life, unsettled relationships, and illiteracy. After adjustment, daytime sleepiness was found to be independently associated with subjects' level of social engagement (odds ratio: 2.5; 95% confidence interval: 1.7–3.8; P < 0.001). Conclusions Daytime sleepiness and poor social engagement are common among aged residents of a veterans' housing facility. Subjects experiencing daytime sleepiness but not poor general sleep quality were at increased risk of poor social engagement. The clinical care of older residents must focus on improving daytime sleepiness to enhance their social engagement.